Cost Recoverable Tariffs to Increase Access to Basic Services among Poor Households - Natalie Chun (Asian Development Bank (ADB), 2013)
The design of alternative tariff structures can serve as a low-cost and effective tool in achieving higher take-up of basic services among poor households while allowing the provider to recover costs. A contingent valuation survey from the Water Supply and Sanitation Project of the Asian Development Bank in Cebu, Philippines is used to show that tariff structures with a low one-time connection price and price differentiates based on wealth measures can result in a five-fold increase in the take-up of water services by poor households over the base tariff structure. More moderate impacts, however, are found for the take-up of new sanitation and sewage services.
hdl:11540/2325
Keywords: D12; D61; D63; O21; 330; Asia; Philippines; water and sanitation services; tariffs; demand estimation; contingent valuation; Wasserversorgung; Kanalisation; Nachfrage; Zahlungsbereitschaftsanalyse; Philippinen; Asien